Comparison of the effects of self-selected music and prefixed music on preoperative anxiety in adults undergoing laparoscopic surgery - K. V Meghana; Pratiti Choudhuri; Amita Gupta; Anju Gupta (The Indian Anaesthetists' Forum)
Background and Aims: Preoperative anxiety can complicate patient outcomes. Music is a noninvasive method to allay anxiety, as revealed in studies. Self-selected (SS) versus prefixed (PF) music had not been studied much. This study was performed to compare SS and PF music in anxiety reduction in patients undergoing elective laparoscopic surgery. Methods: In this prospective study, 90 adults of the American Society of Anesthesiologists grade 1–2, either sex, aged 18–65 years were randomized into three groups, SS, PF music, and control (C), and offered music using headphones 20 min before surgery. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were noted preoperatively (T1), preinduction (T2), 10 min post-induction (T3), 5 min (T4), 1 (T5), and 2 h (T6) postsurgery. The Visual Analog Scale for anxiety (VAS-A) at T1 and T2, VAS-pain and postoperative nausea and vomiting at T5 and T6, and serum cortisol at T1 and T5 were recorded. Results: Group C showed higher VAS-A, HR, SBP, DBP, VAS-pain, and nausea than group-SS and PF (P < 0.05), and higher MAP than group-SS (P < 0.05). The PF group showed higher VAS-A, SBP, DBP, MAP, and VAS-pain than the SS group (P < 0.05). The change in serum cortisol was statistically insignificant. Conclusion: Music (SS > PF) reduces preoperative anxiety, postoperative pain, and nausea–vomiting with better hemodynamic stability.